THE EFFECT OF DIGITAL VISUAL MEDIA USE ON ENGLISH-SPEAKING SKILLS - Aryo Rama Genis Asmiladi; Irwan Sulistyanto; Wawan Hery Setyawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The study aims to examine how well students' English-speaking abilities are affected by digital and visual media. Via a quasi-experimental research design, two groups of primary school pupils were observed: the experimental group received instruction via digital visual media, while the control group received instruction as usual. Pre-test and post-test data were analyzed to determine how much fluency, pronunciation, grammar, vocabulary, and understanding had improved. A statistical analysis using an Independent t-test showed that although the experimental group's mean improvement was 17 points higher than the control group's 9.4 points, the difference was not statistically significant (Sig. = 0.147, p > 0.05). Therefore, it can be suggested that digital visual media creates an urge to learn and enhances the learning outcome; however, it does not significantly impact improving English-speaking skills as per the study's limitations. More extended use of digital media with a larger sample size can be suggested for further studies.